Best Practice in Small School Management Under the Office of the Basic Education Commission, Kamphaengphet Province - et. al., Dr.Yupadee Panarach, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this research was to study best practices in small school management under the office of the Basic Education Commission. The sample acquired by selecting a specific type was a group of small schools under the Office of the Basic Education Commission, Kamphaengphet Province with the results of the National Basic Education Test (O-NET) in Mathematics and Science were higher than the national average in the academic year 2018, namely the mathematics course with a higher average of 37.50 points and science courses with a higher average of 39.93 points. The data were collected by interviews from school directors, teachers and school performance report, including data analysis by analyzing the content. The results showed that 1) for the management namely (1.1) the personnel aspect: the school directors followed-up and encouraged teachers to develop themselves to create a happy learning environment and build morale at work. In addition, teachers always dedicated their time to students and develop themselves. Students had to read and write fluently (1.2) for the support, there was a distance learning system with a teaching manual as well as an internet system to help study and research (1.3) the management, the goals were set for student development and the timetables were arranged for core subjects, secondary subjects and 2) learning management consisted of (2.1) curriculum activities. The teacher analyzed the learners individually , studied indicators and studied the content that had to be taught as well as finding teaching techniques and teaching materials that help learners' interest and fun (2.2) Extracurricular activities, there was an additional teaching after the content was completed by drilling the exam questions that were used for the authentic examination in the past year and took part in the projects with school groups to review together.